2012
DOI: 10.1105/tpc.112.100099
|View full text |Cite
|
Sign up to set email alerts
|

The CRYPTOCHROME1-Dependent Response to Excess Light Is Mediated through the Transcriptional Activators ZINC FINGER PROTEIN EXPRESSED IN INFLORESCENCE MERISTEM LIKE1 and ZML2 in Arabidopsis

Abstract: Exposure of plants to light intensities that exceed the electron utilization capacity of the chloroplast has a dramatic impact on nuclear gene expression. The photoreceptor Cryptochrome 1 (cry1) is essential to the induction of genes encoding photoprotective components in Arabidopsis thaliana. Bioinformatic analysis of the cry1 regulon revealed the putative ciselement CryR1 (GnTCKAG), and here we demonstrate an interaction between CryR1 and the zinc finger GATA-type transcription factors ZINC FINGER PROTEIN EX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 66 publications
(100 reference statements)
0
57
0
Order By: Relevance
“…Upon MeJA treatment, R2R3-MYBs are released by the MeJA-induced degradation of the JAZ proteins, and the target genes are subsequently activated Song et al, 2011). Within the ZML subfamily, Arabidopsis ZML1 and ZML2 can bind DNA, suggesting that these proteins can act as transcriptional regulators (Shaikhali et al, 2012). How ZML factors cooperate with other regulators to activate or repress gene expression and to what extent protein degradation is part of the regulatory function of ZML factors remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Upon MeJA treatment, R2R3-MYBs are released by the MeJA-induced degradation of the JAZ proteins, and the target genes are subsequently activated Song et al, 2011). Within the ZML subfamily, Arabidopsis ZML1 and ZML2 can bind DNA, suggesting that these proteins can act as transcriptional regulators (Shaikhali et al, 2012). How ZML factors cooperate with other regulators to activate or repress gene expression and to what extent protein degradation is part of the regulatory function of ZML factors remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Protoplasts were isolated and transformed with ZTL-Myc or HY5-HA constructs and analyzed as described by Shaikhali et al (2012).…”
mentioning
confidence: 99%
“…This difference in the response to light quality between the ft mutant and the wild type in A. thaliana seems to have commonalities with the difference between 'Bristol Fairy' and 'Million Star' in G. paniculata. We analyzed the G. paniculata homologs of FKF1 (Hori et al, 2011). An E-box and TCTAG motif, which may be important in blue light-dependent FT expression (Liu et al, 2013;Shaikhali et al, 2012), were found in this region from MS.…”
Section: Discussionmentioning
confidence: 99%
“…7). The deleted region contained an E-box (CANNTG) and a TCTAG se- quence, which are reportedly associated with the response to blue light through the CRY pathway (Liu et al, 2013;Shaikhali et al, 2012).…”
mentioning
confidence: 99%